Chitosan-Silica Hybrid Nanomaterials for Oil Spill Treatment - Alimuddin, Alimuddin; Salman, Ahmad Khan; Abdul, Moheman; Mohd Amil, Usmani; Showkat, Ahmad Bhawani (Springer, Singapore, 2025)
Oil spills pose enormous environmental risks, affecting marine ecosystems, wildlife, and coastal towns. In the field of oil spill treatment, chitosan-silica hybrid nanomaterials are a unique approach that has several advantages over conventional techniques. They effectively adsorb oil and other hydrophobic substances from water due to their high surface area and porosity. This adsorption process is reversible; therefore, chitosan-silica hybrid nanomaterials can be recovered and reused. Furthermore, the biodegradable nature of chitosan assures that the adverse effect on the environment is minimized during the cleanup operation. Furthermore, chitosan-silica hybrid nanomaterials can be altered to improve their suitability for oil spill treatments. Studies have shown that chitosan-silica hybrid nanomaterials have significant potential as efficient and recyclable oil absorbents.